The cross-section of Asia-Pacific mortality dynamics: Implications for longevity risk sharing - Biffis,E; Lin,Y; Milidonis,A (Journal of Risk and Insurance, 2017)
We study the dynamics of longevity risk across a subset of countries in the Asia-Pacific (APAC)region. We use hand-collected and existing data on age-specific mortality rates from emergingand developed economies, to understand how secular changesin mortality vary within and acrossAPAC countries. We use our results to identify cross-hedgingopportunities among longevity riskexposures in the APAC region. We also introducek-forward contracts, which offer natural risksharing opportunities to hedgers in different countries. Weconsider the example of Korea andJapan as a case study